Computational design and performance evaluation of green painting absorbing material - Abdullah, Hasnain (2012)
Microwave absorbing materials have received great attention in recent years for both civil and military fields due to various applications in communications, radar, satellite systems, and anechoic chambers.Wireless communication is currently the fastest growth of telecommunication technology.Many studies have indicated that there are harmful radiations produced by transmitting telecommunications structures.Effects on human exposure include dizziness, nausea, vomiting and loss of breath.A way to reduce strong microwave radiations for human is by applying a microwave absorbing paint coating to the wall of the built spaces.The green painting mixed with ingredients from coconut shells is the main material that is analyzed in this research.The findings show that material applied with the green painting can readily absorb the microwave radiations.The wave-absorbing materials are designed by using Computer Simulation Technology (CST) Microwave Studio simulation software.The goal of this simulation is to find the best performing absorber.From dielectric constant value, the modeling and simulation stage of microwave absorber are executed to obtain the reflectivity or S11 result using CST Microwave Studio software.Analysis of the S11 results and measurement of absorber performance are evaluated to define the microwave absorber performance.A free space measurement setup operating in the frequency of Ku Band is employed to measure absorption.The results show that the green painting with coconut based carbon can be used as coating absorbing material.Each material applied with the green painting shows excellent absorption at 3 to 6 dB range.The most excellent result is shown by double layer coating absorption up to 17 dB.